Family Food Security through Urban Farming in Housing Complexes - Anita Kristina; Muhamad Abdul Jumali (STAI Nurul Islam Mojokerto, 2025)
This community service program aims to improve family food security in housing complexes through urban farming. The program involves training and mentoring for residents, specifically residents of RT 13 in the Bumi Candi Asri housing complex, Sidoarjo. Activities include utilizing limited land to grow vegetables and other productive plants. The objectives of this activity are to increase access to healthy and nutritious food, strengthen family food self-sufficiency, and raise awareness of the importance of a sustainable lifestyle. The expected outcome of this activity is to have a positive impact on food security, the economy, and the environment in the housing complex.